Xanthomonas campestris pv. musacearum bacterial infection induces organ-specific callose and hydrogen peroxide production in banana - Sadik Mustafa, Abubakar; Tugume, Benison; Ssenku, Jamilu E.; Ssemanda, Paul; Athman, Shahasi Y.; Oryem-Origa, Hannington; Kubiriba, Jerome; Dinesh-Kumar, Savithramma P.; Tugume, Arthur K. (PhytoFrontiers, 2021)
Xanthomonas campestris pv. musacearum (Xcm) bacteria cause banana Xanthomonas wilt (BXW), the most destructive disease of bananas in East and Central Africa. During early stages of infection in susceptible banana cultivars, incomplete systemic movement of Xcm limits bacterial colonization in the upper organs. Mechanistic basis of this delayed movement is unknown. We hypothesized that Xcm infection triggers basal pattern triggered immune (PTI) responses whose spatial and temporal variability along banana’s anatomical structure accounts for initially limiting Xcm in upper organs. Hence, we examined PTI responses such as callose deposition and hydrogen peroxide (H2O2) production in different organs in response to Xcm infection in BXW susceptible Kayinja and Mbwazirume banana cultivars and wild resistant progenitor Musa balbisiana. Xcm-induced callose increased and peaked at 14 days post inoculation (dpi) and 28dpi as assessed by fluorescence microscopy and enzyme-linked immunosorbent assays, respectively. The levels of Xcm-induced H2O2 and callose were highest in the pseudostems and corms, respectively, and were independent of host susceptibility or resistance to BXW. H2O2 production showed a biphasic transient pattern with an initial increase at 1-hour post Xcm-inoculation (hpi), followed by a decline 3- 6hpi and then a second increase by 12hpi. Our findings point to organ-specific responses to Xcm infection in bananas. The corm which doubles as a subterranean parenating organ and interface between mother plants and lateral shoots, was the most responsive organ in callose production while the pseudostem was the most responsive organ in H2O2 production, suggesting the significance of these organs in banana response to BXW.
Keywords: Banana; Callose; Xanthomonas campestris pv. musacearum; Corm; Musa balbisiana; Hydrogen peroxide; Musa balbisiana; Xcm-mediated defense; Fluorescence microscopy; PAMP- 43 triggered immunity